Σχεδιασμός παραγωγικής μονάδας σκαπτικού βενζινοκίνητου τρακτέρ - Χρυσοστόμου, Πέτρος; Αλεξάνδρου, Αλέξανδρος (Τεχνολογικό Πανεπιστήμιο Κύπρου, 2021)
In this dissertation, the objective is to design a series of gasoline-powered tractors – cultivators and to develop an industrial unit that will be responsible for the production of these tractors. The ultimate goal is to investigate whether such a unit is viable in Cyprus and to study whether there is a possibility of competition with imported tractors of the same category. To achieve the purpose of this dissertation, a tractor that is available on the market was acquired and studied. After important conclusions were drawn from the study, it was decided to create a completely new design which will bring some simplifications in terms of geometry and therefore change the design for improving production. After the design was completed with the help of Solidworks® software, the machines that were necessary for the manufacturing of the parts of the tractors were determined and then, the industrial unit was developed. In addition, the times related to machining were approximately calculated and in later stages the human resources that will be employed in the said unit were determined. Finally, a feasibility study was carried out, the results of which showed that this unit can yield profit and be viable and competitive.
Keywords: development; industrial unit; feasibility study; tractor; machining; design; σχεδιασμός; βιομηχανική μονάδα; τεχνοοικονομική μελέτη; χειροκίνητο τρακτέρ; μηχανικές κατεργασίες